2021
DOI: 10.3390/ijerph18116041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Academic Activity and Health Status among Romanian Medical Dentistry Students; A Cross-Sectional Study

Abstract: During the first year of the COVID-19 pandemic, dental faculties had to rethink their way of teaching and interacting with students and of delivering solid theoretical knowledge and practical skills to students. Background: The purpose of the study was to assess dentistry students’ opinions about the online activity, together with a self-evaluation of their mental and physical health, during the first wave of the pandemic. Methods: A cross-sectional study was conducted using an online survey. Three hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
2
27
0
4
Order By: Relevance
“…Many authors have tried to explore the medical students' and faculty members' perspectives of online learning during the COVID-19 era [8]. As examples, two recent papers by Varvara et al [9] and by Iurcov et al [10] consider the impact of this pandemic on academic activity and health status among medical dentistry students in Romania [9], and also in general dental education challenges during COVID-19 for dentistry undergraduate students in Italy [10]. At present, during the COVID-19 pandemic, e-learning has become a potential approach to technology in education that provides contemporary learners with authentic knowledge acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have tried to explore the medical students' and faculty members' perspectives of online learning during the COVID-19 era [8]. As examples, two recent papers by Varvara et al [9] and by Iurcov et al [10] consider the impact of this pandemic on academic activity and health status among medical dentistry students in Romania [9], and also in general dental education challenges during COVID-19 for dentistry undergraduate students in Italy [10]. At present, during the COVID-19 pandemic, e-learning has become a potential approach to technology in education that provides contemporary learners with authentic knowledge acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results suggested that the unavailability of an online-learning management system (OLMS) was significantly associated with dissatisfaction with online learning among Bangladeshi dental students during the COVID-19 pandemic. Since the shift from on-site classes to online learning was unanticipated and needed swift implementation for education to continue, the rapid development of an efficient OLMS was a challenge during the pandemic [40,[48][49][50][51]. Previous studies reported that an established online educational system can help dental students to improve their theoretical as well as pre-clinical/clinical skills [44,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Since the shift from on-site classes to online learning was unanticipated and needed swift implementation for education to continue, the rapid development of an efficient OLMS was a challenge during the pandemic [40,[48][49][50][51]. Previous studies reported that an established online educational system can help dental students to improve their theoretical as well as pre-clinical/clinical skills [44,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the online theoretical learning ability was considered low among some dental students in Romania despite allocated times to e-learning 92 . However, others have ascertained that dental students in Romania considered online activities a good alternative to face-to-face learning during the pandemic 93 .…”
mentioning
confidence: 99%
“…We are also aware there is increased anxiety among health science students at university, especially those leaving home for the first time without parental support 115 . This situation has typically been exacerbated as a result of the COVID-19 pandemic and associated activities 93,[116][117][118][119][120] . For instance, the forced exclusion from the social aspects of campus life has affected the mental health of students and their learning in Universities in UAE and other Universities 120 , with students among Arab Universities encountering sociocultural challenges with e-learning approaches including privacy concerns among female students with webcams 63,121,122 92 .…”
mentioning
confidence: 99%